Early Development in Duchenne Muscular Dystrophy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1990)
The early development of 33 boys with Duchenne muscular dystrophy (DMD) was assessed at the Institute of Medical Genetics, University of Wales College of Medicine, Heath Park, Cardiff, Wales.